A water-soluble self-repairing binder for lithium-sulfur battery positive electrode, preparation method and application thereof
By designing a high-adhesion self-healing binder LA-GA and utilizing the reaction of lipoic acid and gallic acid, the shuttle effect problem of lithium polysulfide in lithium-sulfur batteries was solved, significantly improving the cycle stability and stability of the battery. life.
Patent Information
- Application Number
- CN202410671003.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-28
AI Technical Summary
Due to the inherent dissolution and shuttle phenomenon of lithium polysulfide in ether-based electrolytes, lithium sulfur batteries have poor cycle stability, rapid decline in capacity and shortened life.
A self-healing adhesive LA-GA with high adhesion was designed and prepared through the ring-opening polymerization of lipoic acid and the sulfur radical-polyphenol Michael addition reaction between polylipoic acid and gallic acid. The binder introduces a pyrogallol structure to stabilize the polylipoic acid skeleton and enhance adhesion. The abundant polar carboxyl and hydroxyl groups are beneficial to anchoring lithium polysulfide and inhibiting the shuttle effect.
It significantly improves the structure and electrochemical stability of the lithium-sulfur battery cathode, improves the battery's cycle stability and capacity retention, and extends the battery's life.
Smart Images

Figure CN118652658B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a water-soluble self-repairing binder for a lithium-sulfur battery positive electrode, a preparation method and application thereof, which can be used in new energy vehicles, etc., and belongs to the technical fields of self-repairing materials, lithium-ion battery monomers, etc. Background Art
[0002] Today, the global environmental pollution problem is becoming increasingly serious, and fossil energy resources are facing rapid depletion. To address this challenge, humans are actively exploring the best way to replace traditional fossil energy with clean energy. Under the initiative of "carbon peak" and "carbon neutrality", all sectors of society have paid attention to the development and exploration of clean energy. Lithium-sulfur (Li-S) batteries have a high capacity of up to 2600Whkg -1 The ultra-high theoretical energy density, abundant natural resources and environmental friendliness of lithium-sulfur batteries show great potential in the emerging field of energy storage systems. However, due to the inherent dissolution and shuttling of lithium polysulfide in ether-based electrolytes, coupled with the volume expansion caused by the conversion of sulfur active substances into lithium sulfide, the battery has poor cycle stability, resulting in a rapid decrease in capacity and a significantly shortened lifespan. These major challenges hinder the future commercialization of lithium-sulfur batteries.
[0003] In order to better solve the above problems, it is necessary to prepare high-performance lithium-sulfur battery binders. As an important component of the sulfur positive electrode, the main function of the binder is to bind the active material particles, the conductive agent and the current collector to ensure the integrity and stability of the positive electrode structure during the cycle. At the same time, the binder also plays an important role in the homogenization process of the electrode slurry, the flexibility of the electrode, the cycle stability of the battery, etc. Studies have shown that the development of new high-performance binders can effectively solve the problem of battery performance attenuation caused by the large-scale dissolution and shuttling of polysulfides. At present, polyvinylidene fluoride (PVDF) is widely used as a binder for commercial lithium-ion batteries due to its excellent electrochemical stability. However, when it is applied to lithium-sulfur batteries, only weak interactions are formed between PVDF and lithium polysulfide, which results in PVDF being unable to effectively inhibit the shuttling effect of lithium polysulfide. In addition, N-methyl-2-pyrrolidone (NMP) used to dissolve PVDF is toxic, environmentally harmful and expensive. At the same time, when the electrode containing NMP is dried at high temperature, the loss of sulfur active substances may occur. Therefore, the development of high-performance lithium-sulfur battery positive electrode water-soluble self-healing binders has become a hot topic of research. Summary of the invention
[0004] In order to solve the inherent dissolution and shuttling of lithium polysulfide in ether-based electrolytes, coupled with the volume expansion of sulfur active substances converted into lithium sulfide, the present invention designs and prepares a self-healing binder LA-GA with high adhesion through the ring-opening polymerization reaction of lipoic acid and the sulfur radical-polyphenol Michael addition reaction between polylipoic acid and gallic acid. Linear polylipoic acid is selected as the skeleton, and the pyrogallol structure is introduced as a polylipoic acid terminal sulfur radical quencher, which helps to stabilize the polylipoic acid skeleton and enhance adhesion. It is worth noting that the abundant polar carboxyl and hydroxyl groups in LA-GA are conducive to anchoring lithium polysulfide, thereby inhibiting the shuttle effect. It is applied to the positive electrode of lithium-sulfur batteries in order to improve the structure and electrochemical stability of the positive electrode.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A water-soluble self-repairing binder for a lithium-sulfur battery cathode, having the structural formula: The value range of n is 1.1 to 100.
[0007] The wavy lines in the above structural formula are omitted repeating units.
[0008] The above-mentioned water-soluble self-repairing binder for the positive electrode of lithium-sulfur battery is rich in biomass, has a wide source of raw materials, is renewable and sustainable.
[0009] The above-mentioned lithium-sulfur battery positive electrode water-soluble self-repairing binder, its raw material components are composed of gallic acid, polylipoic acid formed by polymerization of lipoic acid monomers and lithium hydroxide aqueous solution. No additives such as inorganic iron salts and cross-linking agents are required during preparation. The mass ratio of gallic acid to lipoic acid is (8-10):100, and the mass ratio of lithium hydroxide to gallic acid is (1.22-1.32):1.
[0010] The use of lithium hydroxide to partially lithiate lipoic acid significantly improves its water solubility, so that it does not need to react under high-temperature melting conditions, and does not need to add inorganic iron salts, cross-linking agents and other substances. The generated product is extremely water-soluble, not gel-like, and is extremely easy to handle, making it suitable as a positive electrode binder for lithium-sulfur batteries.
[0011] Lipoic acid is a small molecule containing endogenous disulfide bonds that exists in animal and plant tissues. It has the advantages of rich hydroxyl groups, sufficient reserves, renewable, and environmentally friendly. Lipoic acid contains high-performance binders with polar functional groups that can effectively reduce the shuttling effect of lithium polysulfide. However, in the process of using lipoic acid to prepare polymers, due to the presence of terminal sulfur free radicals, reverse depolymerization reactions may occur to form oligomeric polylipoic acid opaque crystals. Therefore, when using lipoic acid to prepare high-performance binders, it is necessary to overcome the metastable state of polylipoic acid. Gallic acid is a water-soluble polyphenol compound containing a pyrogallol structure. The pyrogallol structure in gallic acid is used to quench the sulfur free radicals in polylipoic acid, thereby obtaining a stable polymerization product. The polymer prepared by such a composite system not only maintains the original self-healing ability, but also enhances key properties such as adhesion strength.
[0012] The mass concentration of the lithium hydroxide aqueous solution is 5-10wt%.
[0013] The polylipoic acid is obtained by heat-induced ring-opening polymerization of lipoic acid monomer at 60-70°C.
[0014] The preparation method of the water-soluble self-repairing binder for the positive electrode of the lithium-sulfur battery is as follows: at room temperature, lipoic acid and gallic acid (GA) are added to a lithium hydroxide aqueous solution in sequence to react, thereby obtaining the water-soluble self-repairing binder for the positive electrode of the lithium-sulfur battery. No additives such as inorganic iron salts and cross-linking agents are required during the preparation process, which is simple, efficient, low-cost and has good performance.
[0015] In order to further improve the bonding performance, the preparation method of the water-soluble self-repairing binder for the positive electrode of the lithium-sulfur battery is as follows: at room temperature, thioctic acid is added to a lithium hydroxide aqueous solution, the temperature is raised to 60-70°C, and the reaction is carried out for 0.3-0.5h, and then gallic acid is added, and the reaction is continued at 60-70°C for 1.5-2.5h to obtain the water-soluble self-repairing binder for the positive electrode of the lithium-sulfur battery. That is, the thioctic acid monomer undergoes ring-opening polymerization and reacts with lithium hydroxide, and then reacts with gallic acid.
[0016] The mass concentration of the lithium hydroxide aqueous solution is 1-5wt%.
[0017] The above-mentioned lithium-sulfur battery positive electrode water-soluble self-healing binder is used as a lithium-sulfur battery positive electrode water-soluble self-healing binder, provides bonding and self-healing effects, adsorbs and anchors lithium polysulfide, inhibits the shuttle effect, enhances electrochemical performance, and improves stability and integrity.
[0018] The water-soluble self-repairing binder for the positive electrode of the lithium-sulfur battery is mixed with a conductive agent, a positive electrode active material and a dispersant by ball milling to form a slurry, which is then coated on a current collector with a coating thickness of 50 to 150 μm. After heating and drying at 60 to 100° C., a positive electrode of the lithium-sulfur battery is obtained.
[0019] As one of the preferred implementation schemes, the conductive agent is acetylene black, Super P, carbon nanotubes or graphene; the dispersant is N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or water (H 2 O); the current collector is aluminum foil.
[0020] Further preferably, the specific method of using the above-mentioned lithium-sulfur battery positive electrode water-soluble self-repairing binder is to grind the lithium-sulfur battery positive electrode water-soluble self-repairing binder, the conductive agent and the positive electrode active material at a ball milling speed of 500 to 2200 r min according to the mass ratio of positive electrode active material: conductive agent: lithium-sulfur battery positive electrode water-soluble self-repairing binder = (6 to 9): (2 to 0.5): (2 to 0.5). -1 The electrode slurry is mixed and treated for 15 to 60 minutes under the conditions of , and a solid content of 20 to 50% is obtained. The electrode slurry is coated on the aluminum current collector with a coating thickness of 120 to 150 μm, and vacuum heated and dried at 60 to 100 ° C to obtain a battery positive electrode; the active material loading is 1.0-7.0 mg cm -2 .
[0021] The binder prepared by the present invention has more action sites with the active material. The modified binder not only has polar functional groups, but also exhibits stronger electrode bonding performance, which can effectively maintain the stability of the sulfur positive electrode structure, bind polysulfides in the positive electrode area, prevent the diffusion of polysulfides, and significantly improve the electrochemical performance of lithium-sulfur batteries. Compared with lithium-sulfur batteries based on traditional binder PVDF, the lithium-sulfur battery prepared by the binder of the present invention has significantly improved initial discharge specific capacity and cycle stability.
[0022] The technologies not mentioned in the present invention are all referred to the prior art.
[0023] The present invention has the following beneficial effects:
[0024] (1) The present invention provides a lithium-sulfur battery binder, specifically a binder based on a polyphenol compound-polymer composite system. The binder has abundant dynamic SS bonds, which endows it with excellent self-healing ability; the end group of the polymer chain introduces gallic acid with a pyrogallol structure, which is expected to significantly improve the adhesion effect of the polymer; the introduction of the GA pyrogallol structure enables the LA-GA polymer to have excellent bonding strength and self-healing properties, significantly improving the stability and integrity of the sulfur positive electrode structure.
[0025] (2) Due to the large amount of dissolution and shuttling of polysulfides, as well as the volume expansion caused by the conversion of sulfur into lithium sulfide, the battery performance will decay rapidly. Due to the deprotonation treatment, the binder provided by the present invention has a large number of polar lithium carboxylate groups in the polymer chain. These polar groups can effectively adsorb polysulfides, thereby limiting their dissolution and shuttling in the electrolyte, thereby enhancing their electrochemical performance, so that the positive electrode exhibits higher redox reaction kinetics and lithium ion diffusion rate, and has good rate performance.
[0026] (3) Safe and pollution-free water is used as the solvent, the raw material consumption is small, the reaction temperature is low, and there is no need to add inorganic iron salts, cross-linking agents, etc., so the preparation is simple and safe. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The preparation route and molecular structure diagram of the lithium-sulfur battery binder provided in the example.
[0028] Figure 2 Infrared spectra of the lithium-sulfur battery binders provided in Example 1 and Comparative Example 2.
[0029] Figure 3 Raman spectra of the lithium-sulfur battery binders provided in Example 1 and Comparative Example 2.
[0030] Figure 4 The battery cycle stability test pictures provided for Example 1 and Comparative Example 1.
[0031] Figure 5 Scanning electron microscope photos of electrodes provided for Example 1 and Comparative Examples 1 and 2.
[0032] Figure 6 Optical images of the self-healing properties provided in Example 1 and the mechanical properties at different healing times.
[0033] Figure 7 The adsorption performance test provided for Example 1 and Comparative Example 1 and Comparative Example 2.
[0034] Figure 8 The rate performance test provided for Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0036] In each case, the same raw materials, sources, models, etc. are the same and are from the same batch. In each case, if the temperature is not specified, it is carried out at room temperature (15-25°C); the stirring speed is 300 r min -1 .
[0037] Comparative Example 1
[0038] A method for preparing a lithium-sulfur battery comprises the following steps:
[0039] (1) First, sulfur powder (70 wt %, Aladdin Reagent Co., Ltd., 99.99%) and Ketjen black (30 wt %, Kruder New Energy Technology Co., Ltd., battery grade) were mixed to prepare a sulfur / Ketjen black (S / KB) composite material, and then heated at 155 ° C for 12 h in an argon atmosphere. Then, 0.20 g, 0.025 g, and 0.025 g of the S / KB composite material, carbon nanotubes (Kruder New Energy Technology Co., Ltd., battery grade), and PVDF binder (Kynar, HSV900) were weighed at a mass ratio of 8:1:1, 1.25 g of NMP was added, and the mixture was milled in a ball mill at 1000 r min. -1 Mix at a speed of 20 min and at 500 r min -1 The slurry was mixed at a speed of 10000rpm for 10 minutes to obtain a viscous slurry. The slurry was coated on aluminum foil using a scraper and vacuum dried at 60°C for 24 hours to remove the solvent. The dried electrode was punched into The disc is used as the working electrode and as the positive electrode of the lithium-sulfur battery.
[0040] (2) In a glove box filled with argon, the electrode sheet prepared in step (1) is used as the positive electrode, the metal lithium sheet is used as the negative electrode, and the electrolyte is composed of 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt dissolved in 1,3-dioxolane (DOL) / 1,2-dimethoxymethane (DME) in a volume ratio of 1:1, containing an additive of 2% LiNO 3 (LS009) (i.e., the electrolyte is 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt solution, the solvent used is 1:1 1,3-dioxolane (DOL) / 1,2-dimethoxymethane (DME), and the electrolyte also contains 2 wt% LiNO 3 ), and assembled into CR2032 standard button cells using Celgard-2500 commercial separators. After the battery was left to stand for 12 hours, a charge and discharge cycle test was performed using a Blue Power battery test system at a current density of 1.0C, with charge and discharge cut-off voltages of 2.8V and 1.7V.
[0041] Comparative Example 2
[0042] A method for preparing a lithium-sulfur battery binder comprises the following steps:
[0043] First, 0.216 g of LiOH was dissolved in 6.0 g of deionized water. Subsequently, 2.06 g of LA (thioctic acid) was added and stirred at 70 ° C for 3.0 h to perform a ring-opening polymerization reaction to obtain a polythioctic acid aqueous solution. Finally, the obtained solution was poured into a polytetrafluoroethylene mold and then dried in an oven at 50 ° C to constant weight to obtain a LA polymer film. The infrared spectrum is shown in FIG. Figure 2 As shown in the Raman spectrum Figure 3 shown.
[0044] A method for preparing a lithium-sulfur battery comprises the following steps:
[0045] (1) First, sulfur powder (70 wt%) and Ketjen black (30 wt%) were mixed to prepare a sulfur / Ketjen black (S / KB) composite material, which was then heated at 155 °C for 12 h in an argon atmosphere. Then, 0.20 g, 0.025 g, and 0.025 g of the S / KB composite material, carbon nanotubes, and LA polymer film were weighed at a mass ratio of 8:1:1, respectively, and 1.25 g of deionized water was added. The mixture was first milled in a ball mill at 1000 r min -1 Mix at a speed of 20 min and at 500 r min -1 The slurry was mixed at a speed of 10000rpm for 10 minutes to obtain a viscous slurry. The slurry was coated on aluminum foil using a scraper and vacuum dried at 60°C for 24 hours to remove the solvent. The dried electrode was punched into The disc is used as the working electrode and as the positive electrode of the lithium-sulfur battery.
[0046] (2) In a glove box filled with argon, the electrode sheet prepared in step (1) is used as the positive electrode, the metal lithium sheet is used as the negative electrode, and the electrolyte is composed of 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt dissolved in 1,3-dioxolane (DOL) / 1,2-dimethoxymethane (DME) in a volume ratio of 1:1, containing an additive of 2% LiNO 3 (LS009), using Celgard-2500 commercial separator to assemble into CR2032 standard button cell. After the battery was left to stand for 12 hours, the charge and discharge cycle test was performed using the Blue Power Battery Test System at a current density of 1C, with the charge and discharge cut-off voltages of 2.8V and 1.7V.
[0047] Example 1
[0048] A method for preparing a lithium-sulfur battery binder, such as Figure 1 As shown, the following steps are included:
[0049] First, 0.216 g of LiOH was dissolved in 6 g of deionized water. Subsequently, 2.06 g of LA was added and stirred at 70 ° C for 0.5 h for ring-opening polymerization to obtain a polylipoic acid polymer aqueous solution. Subsequently, 0.17 g of GA was added and stirred at 70 ° C for 2.5 h. Finally, the obtained solution was poured into a polytetrafluoroethylene mold and then dried in an oven at 50 ° C to constant weight to obtain a LA-GA polymer film. The infrared spectrum is shown in FIG. Figure 2 As shown in the Raman spectrum Figure 3 shown.
[0050] A method for preparing a lithium-sulfur battery comprises the following steps:
[0051] The S / KB composite material (prepared with reference to comparative example 2), carbon nanotubes and LA-GA polymer film were weighed at a mass ratio of 8:1:1, 0.20 g, 0.025 g and 0.025 g, respectively, and 1.25 g of deionized water was added. The mixture was first milled in a ball mill at 1000 r min -1 Mix at a speed of 20 min and at 500 r min -1 The mixture was mixed at a speed of 10000rpm for 10 minutes to obtain a viscous slurry. The remaining steps were the same as those in Comparative Example 2.
[0052] Comparative Example 3
[0053] Prepare the adhesive as follows:
[0054] 1) Add 1.25 g of lipoic acid (LA) into a glass bottle and heat at 150° C. to form a uniform and transparent melt;
[0055] 2) under magnetic stirring, tannic acid having a mass of 4% of the mass of lipoic acid is added to the melt of step (1),
[0056] React at 150°C to form a uniform mixed melt;
[0057] 3) Ferrous chloride (FeCl 3 ) According to n(LA):n(FeCl 3 )=50:1 in a molar ratio into the melt of step (2), react at 150° C. to form a uniform mixed melt;
[0058] 4) The stable melt in step (3) is then cooled to room temperature. The obtained sample is a gel that is insoluble in water and cannot be used as a binder for lithium-sulfur batteries.
[0059] The above embodiments and comparative examples were tested for bonding performance:
[0060] The dried electrode was cut into test samples of 20×40 mm in size. The samples were fixed on the stainless steel plate of the test machine using an electronic tensile tester according to GB / T2792-2014. The side coated with the positive electrode material was taped at 20 mm / min. -1 The sample was peeled off at 180° at a constant speed to test its peeling force.
[0061] Battery cycle stability test Figure 4 The scanning electron microscope photo of the electrode is shown in Figure 5 shown.
[0062] After a clear scratch was made on the sample with a scalpel, it was placed at room temperature without applying external force. The healing of the scratch on the sample was observed using an optical microscope at healing times of 0 h, 3 h, and 6 h. The self-healing properties were as follows: Figure 6 shown.
[0063] Sublimed sulfur (S) and lithium sulfide (Li 2 S) was added to a DME / DOL (v / v=1:1) solution at a molar ratio of 5:1, and then stirred at 70°C for 24 h under an Ar atmosphere to obtain 0.25 M Li 2 S 6 Solution. Take 0.25M Li 2 S 6 100 μL of the solution was dissolved in 4.9 mL of 1,2-dimethoxyethane (DME) / 1,3-dioxolane (DOL) (v / v = 1:1) solution to form a blank Li 2 S 6 The adsorption experiment was carried out by adding 100 mg of different binders to the blank solution and photographing the color change of the solution after standing for 12 hours. At the same time, the spectrum from 350 to 600 nm was recorded using a UV-visible spectrometer. Figure 7 shown.
[0064] The rate performance of the positive electrode of the embodiment and the positive electrode of comparative example 1 at different current densities (0.1, 0.2, 0.5, 1.0 and 2.0C) is as follows: Figure 8 shown.
[0065] Table 1: Test results of lithium-sulfur battery cathodes prepared using different binders
[0066]
Claims
1. A water-soluble self-repairing binder for a lithium-sulfur battery cathode, characterized in that: Its structural formula is: , where n ranges from 1.1 to 100; In the raw materials of the water-soluble self-healing binder for the positive electrode of lithium-sulfur batteries, the mass ratio of gallic acid to lipoic acid is (8~10):
100.
2. The water-soluble self-repairing binder for lithium-sulfur battery cathode according to claim 1, characterized in that: Its raw material components consist of gallic acid, polylipoic acid formed by polymerization of lipoic acid monomers and lithium hydroxide aqueous solution, without the need for inorganic iron salts and cross-linking agents, and the mass ratio of lithium hydroxide to gallic acid is (1.22~1.32):
1.
3. The water-soluble self-repairing binder for lithium-sulfur battery cathode according to claim 2, characterized in that: The mass concentration of the lithium hydroxide aqueous solution is 1~5wt%.
4. The water-soluble self-repairing binder for lithium-sulfur battery cathode according to claim 2 or 3, characterized in that: Polylipoic acid is obtained by thermally induced ring-opening polymerization of lipoic acid monomer at 60-70 °C.
5. A method for preparing the water-soluble self-repairing binder for lithium-sulfur battery positive electrode according to any one of claims 1 to 4, characterized in that: At room temperature, lipoic acid and gallic acid are added in sequence to a lithium hydroxide aqueous solution to react, thereby obtaining a water-soluble self-repairing binder for the positive electrode of a lithium-sulfur battery.
6. The method for preparing the water-soluble self-repairing binder for lithium-sulfur battery cathode according to claim 5, characterized in that: At room temperature, thioctic acid is added to a lithium hydroxide aqueous solution, the temperature is raised to 60-70 °C, and the reaction is carried out for 0.3-0.5 h. Subsequently, gallic acid is added and the reaction is continued at 60-70 °C for 1.5-2.5 h to obtain a water-soluble self-repairing binder for the positive electrode of a lithium-sulfur battery.
7. The method for preparing the water-soluble self-repairing binder for lithium-sulfur battery cathode according to claim 5 or 6, characterized in that: The mass concentration of the lithium hydroxide aqueous solution is 5-10 wt %; the mass ratio of gallic acid to thioctic acid is (8-10):100, and the mass ratio of lithium hydroxide to gallic acid is (1.22-1.32):
1.
8. An application of the water-soluble self-repairing binder for lithium-sulfur battery positive electrode according to any one of claims 1 to 4, characterized in that: Used as a water-soluble self-healing binder for the positive electrode of lithium-sulfur batteries, it provides bonding and self-healing effects, adsorbs and anchors lithium polysulfide, inhibits the shuttle effect, enhances electrochemical performance, and improves stability and integrity; The water-soluble self-repairing binder for the positive electrode of the lithium-sulfur battery is mixed with a conductive agent, a positive electrode active material and a dispersant by ball milling into a slurry, and then coated on a current collector with a coating thickness of 50 to 150 μm; after heating and drying at 60 to 100 ° C, a positive electrode of the lithium-sulfur battery is obtained.
9. The use of the water-soluble self-repairing binder for lithium-sulfur battery cathode as claimed in claim 8, characterized in that: The conductive agent is acetylene black, Super P, carbon nanotube or graphene; the dispersant is N-methylpyrrolidone, N,N-dimethylformamide or water; and the current collector is aluminum foil.
10. The use of the water-soluble self-repairing binder for lithium-sulfur battery cathode according to claim 8 or 9, characterized in that: According to the mass ratio of positive electrode active material: conductive agent: lithium-sulfur battery positive electrode water-soluble self-repairing binder = (6-9): (2-0.5): (2-0.5), the lithium-sulfur battery positive electrode water-soluble self-repairing binder, the conductive agent and the positive electrode active material are ball milled at a speed of 500-2200 r min −1 The mixture was mixed for 15-60 min under the conditions of , to obtain an electrode slurry with a solid content of 20-50%, the electrode slurry was coated on the aluminum current collector with a coating thickness of 120-150 μm, and the battery positive electrode was obtained by heating and drying at 60-100 °C in vacuum; the active material loading was 1.0-7.0 mgcm −2 .
Citation Information
Patent Citations
Biodegradable polyethylene glycol based water-insoluble hydrogels
CN102573913A
Silicon-based active material particles for secondary battery and method for producing same
CN109843799A